Contributions civilistes à l’interprétation des lois constitutionnelles canadiennes - Boulanger-Bonnelly, Jérémy (McGill Law Journal, 2025)
While the interpretation of Canadian constitutional laws has long been carried by a teleological wave, a textualist backlash has emerged in recent years. This article questions this trend and argues that the teleological method remains the most appropriate for constitutional interpretation.